Analgesic, Anxiolytic and Anaesthetic Effects of Melatonin: New Potential Uses in Pediatrics - Marseglia, Lucia (Int J Mol Sci, 2015)
Exogenous melatonin is used in a number of situations, first and foremost in the treatment of sleep disorders and jet leg. However, the hypnotic, antinociceptive, and anticonvulsant properties of melatonin endow this neurohormone with the profile of a drug that modulates effects of anesthetic agents, supporting its potential use at different stages during anesthetic procedures, in both adults and children. In light of these properties, melatonin has been administered to children undergoing diagnostic procedures requiring sedation or general anesthesia, such as magnetic resonance imaging, auditory brainstem response tests and electroencephalogram. Controversial data support the use of melatonin as anxiolytic and antinociceptive agents in pediatric patients undergoing surgery. The aim of this review was to evaluate available evidence relating to efficacy and safety of melatonin as an analgesic and as a sedative agent in children. Melatonin and its analogs may have a role in antinociceptive therapies and as an alternative to midazolam in premedication of adults and children, although its effectiveness is still controversial and available data are clearly incomplete.